2021
DOI: 10.1039/d1ra06474f
|View full text |Cite
|
Sign up to set email alerts
|

An aqueous two-phase system formed in single-component solution of α-ketooctanoic acid

Abstract: An aqueous two-phase system can form in the single-component solution of α-ketooctanoic acid without any additives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Figure 3(d1) showed that the aggregates in the turbid upper phase were stacked lamellar structures. No large aggregates were observed in the transparent lower phase (Figure 3(d2)), indicating the formation of small micelles [7,13,18] above critical micelle concentration [24], which is consistent with the limpidity of the solution. The existence of micelles was further detected by DLS (Figure S1), showing that micelle aggregates formed in the lower phase with ca.…”
Section: Microscopy Observationsupporting
confidence: 69%
See 2 more Smart Citations
“…Figure 3(d1) showed that the aggregates in the turbid upper phase were stacked lamellar structures. No large aggregates were observed in the transparent lower phase (Figure 3(d2)), indicating the formation of small micelles [7,13,18] above critical micelle concentration [24], which is consistent with the limpidity of the solution. The existence of micelles was further detected by DLS (Figure S1), showing that micelle aggregates formed in the lower phase with ca.…”
Section: Microscopy Observationsupporting
confidence: 69%
“…Herein, three types of PA species coexist, i.e., non-ionized (neutral acid, RCOOH), ionized (deprotonated carboxylate soap, RCOO − ) species, as well as the "acid-soap" dimers formed through hydrogen bonding between the two species. Similar to most fatty acid systems, it is the dimers that lead to the formation of various bilayer structures [18,51,52]. As R increased, the ionization degree (or relative content of RCOO − ) increased, and the contents of RCOOH decreased.…”
Section: Effect Of the Molar Ratio R At The Molecular Scale: Ionizati...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the scattering factor ratio (q1/q2) of the red curve in the 8 wt % n -dodecane system was approximately 1:2, indicating the presence of a lamellar micelle microstructure . Additionally, the Maltese cross pattern was also observed through the POM as the characteristic of a typical layered liquid crystal (Figure b) . Both of these findings indicated the existence of lamellar micelles within the system.…”
Section: Resultsmentioning
confidence: 78%
“…26 Additionally, the Maltese cross pattern was also observed through the POM as the characteristic of a typical layered liquid crystal (Figure 6b). 48 Both of these findings indicated the existence of lamellar micelles within the system.…”
Section: ■ Introductionmentioning
confidence: 99%